Supporting gender identity and sexual orientation diversity in K-12 schools - Lytle, Megan C.; Sprott, Richard A., 1965- (Perspectives on sexual orientation and gender diversity series., 2021)
"This book reviews timely, pragmatic interventions and strategies to support LGBTQ students in K-12 schools. Where formal programs affirming diversity of gender expression and sexual orientation are not yet in place, contributors provide insights and practical tips for creating a positive, safe school environment. Topics include how stigma based on gender expression or sexual orientation can affect children and adolescents in school performance and risk-taking behavior, and how schools can flip the narrative on bullying and victimization to one that promotes strengths and school connectedness. Teacher and school staff training issues are also addressed, along with suggestions for advocacy on the small scale and at local, regional, and state systems levels. In this book school counselors and psychologists, administrators, teachers, and other community stakeholders will find steps they can take to translate and implement the ever-growing body of scientific theory and research on equitable education of gender minority and sexual minority children, youth, and families"--